The radical potential of leaks in the shadow accounting project: The case of US oil interests in Nigeria - Andrew, Jane; Baker, Max (Accounting, Organizations and Society, 2020)
This paper explores the ways in which leaked documents can be recruited to contribute to the counter-hegemonic aims of the shadow accounting project. Drawing on material published by Wikileaks as part of Cablegate, our case study focuses on private communication between US Embassy officials about Chevron Nigeria from 2002 to 2010. In analyzing these documents, we mobilize the ideas of both Laclau and Mouffe (1985) and Jessop (1990), emphasizing the role discourse plays in the production and maintenance of hegemonic coalitions between powerful state and market actors, which are central to neoliberalism. Our analysis suggests that the sharing of discourse, much of which occurs in private, allows a hegemonic coalition to agree to a “’popular-national’ programme” (Jessop, 1990) that serves the interests of the coalition, while masquerading as collectively beneficial. In our case study, this private discourse provided the means through which the “moral and intellectual leadership” of the coalition could be embedded in a shared commitment to the maintenance of oil production in Nigeria, despite significant resistance from local communities. In choosing to use leaks to explore the state-capital nexus, we offer a shadow account of the discursive production of hegemony that reveals it to be an ongoing and active project. Importantly, we also show that the very act of creating and recreating hegemony through discourse produces moments of vulnerability and fragility that present counter-hegemonic opportunities. When leaks are mobilized to produce shadow accounts of the contradictions and tensions that exist between the state and capital, the “political frontier” can be restored in ways that re-politicize and radicalize democracy (Mouffe, 2018, p. 4).